Strength Characteristics of Fe-SMA Reinforcement in RC Beam with Experimentation and Finite Element Modeling - Jadhav, Priyanka; Gite, Archana; Wankhade, Rajan L. (Communications - Scientific Letters of the University of Zilina, 2023)
The work presented here aims at investigating the feasibility of iron-based Fe-SMA (shape memory alloy) reinforcement as an alternative to conventional steel reinforcement. The conventional steel reinforcement shows large plastic strain, low resistance to corrosion, low resistance to fatigue and also inadequate recentering capability. As a result, advanced materials available in the form of superelastic (SE) shape memory alloy (SMA) are fabricated to form structural reinforcements. This FE-SMA mitigates the problem of long-lasting deflection by using its reversible stress-strain capability. This iron-based Fe-SMA may be stimulated between the temperatures of 90 to 150°C, with which it is possible to strengthen the reinforced concrete (RC) beams without any crucial damage. The stress-strain behavior in tension, corrosion resistivity, pull-out tests of Fe-SMA reinforcement and flexural strength of RC beam were evaluated experimentally. The FE-SMA exhibits recovery stresses of 250-300 MPa subjected to a temperature of 160°C. A comparison of load-carrying capacity of iron-based Fe-SMA reinforcement is also shown.
Keywords: Fe-SMA; RC beam; flexural strength; stress-strain relationship